ANALISIS PENGARUH BAURAN PEMASARAN ECERAN TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Pada Distro Resist Wear Turen Malang) - Magdalena Dwi Anggraini; Rois Arifin; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThe purpose of research are to determine whether there is asimultaneous influence between the retail marketing mix consisting of, product,price, place, promotion, in-store atmosphere and service to purchase decision atResist Wear Turen Malang Distribution and to find out whether there is partialinfluence between the mix marketing consisting of, product, price, place,promotion, in-store atmosphere and service to purchasing decision at Resist WearTuren Malang Distribution. By using analysis tool that is doubled linearregression.Based on research and discussion in this research that can be drawn theconclusion that the retail marketing mix consisting of, product, price, place,promotion, store atmosphere and service to purchase decision at Resist WearTuren Malang Distribution, can influence simultaneously to decision purchase ofResist Wear Turen Malang Distribution. Mix of retail marketing consisting of,product, price, place, promotion, atmosphere in store and service to purchasingdecision at Resist Wear Turen Malang Distribution that can influence partiallythat is only place and atmosphere in store.Keywords: Retail Marketing Mix and Purchase Decision.